A institucionalização dos partidos políticos na Argentina e no Brasil pós-terceira onda de democratização: uma análise comparada - Rodrigues, Marcus Leonardo Corrêa (2015)
This work has the objective of studying the political parties institutionalization process in Argentina and Brazil since the democratization until the 2000s. To an analysis aimed to historical and institutional aspects, it sought to evaluate the effects of these variables on the institutionalization and the internal dynamics of the greatest legends that form the Argentinian and Brazilian party systems, namely PJ and UCR, PFL, PMDB, PSDB and PT respectively. To deal with the analytical purposes at hand, resorted to the policy of the methodology compared with the contribution of the historical neo-institutionalism and neo-institutionalism of rational choice. With comparative analysis aims to identify similarities and/or differences between the cases. Already with the historical neo-institutionalism it is emphasized the importance of the historical trajectory of the political parties and with the neo-institutionalism of rational choice, emphasize the molding influence of institutional rules on political outcomes. Finally, the findings of this study show that, in a broad sense, despite the severe crisis of representation, which to a large extent, affects all parties, they still have a satisfactory ability to structure party systems of the screen countries.